ENHANCING ACADEMIC PERFORMANCE & SOCIAL EMOTIONAL LEARNING (SEL) WITH THE BRAIN ENHANCEMENT PROGRAM (â€œBTEâ€) - Chirag Bhikamchand Jain; Darshana Chirag Jain, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Social Emotional Learning is a core competency in the coming future as mankind has created and invented a gadget, device or an app for almost most of technical and knowledge-based needs. Especially during the pandemic, the need for SEL programs becomes a necessity. The important process then remains to create individuals with sensitivity to navigate in such endowed systems, without feeling too powerful or at the polar end without feeling disconnected. It is undeniable society at large will be living with this sense of having the world at their fingertips! It is exactly because of this reason that it is necessary to be socially emotionally adjusted to co-exist with many such equally gifted or talented people around oneself. At the same time the children are exposed to the fast-paced world and ever demanding need to excel and perform better academically. The Brain Training Enhancement Program (â€œBTEâ€) is a scientifically designed well researched program using Neurofeedback to improve the brain ability of students in competitive exams. The A pre- and post-test quasi-experimental design was used to test the impact of a 10-week, online-based social and emotional learning (SEL) intervention, Brain Training Enhancement Program (â€œBTEâ€), on the academic performance and social and emotional competence of 12th grade students (N =82) in two classrooms in one school. Academic performance was assessed by report card grades done in the immediate past and immediately post intervention. Social and emotional competence was assessed with Psychometric Analysis and QEEG Measurements. Students in classrooms integrating BTE program had higher year-end grades and higher scores of social and emotional competences (e.g., Engagement, Self-Regulation, and Focus) compared to students in the comparison group. This study provides preliminary empirical evidence that SEL programs like BTE improve important student outcomes.